Computer experimentation with an energy-based simulation model of animal production in the eastern savannas of Colombia - Thornton, Philip K. (1989)
Results of preliminary experimentation with a computer based simulation model of beef production in theEastern Savannas of Colombia are reported The energetic consequences of various uses of sown pasturesare examined with reference to their long term biological feasibility The quality of grass legume mixturescurrently under evaluation at the International Centre for Tropical Agriculture is such that the availability of energy in the extensive animal production systems is limiting during the dry season as it is for traditionalsavanna based production systems A number of options are identified which appear to ameliorate thisconstraint Dual purpose beel and milk systems based on the use of sown pastures are viabie and productiveowing to the increased availability of energy in the wet season.